Mechanism of anti-cancer activity of (z)-3-hydroxy-1-(2-hydroxyphenyl)-3-phenylprop–2–en-1-one (DK1) in human osteosarcoma cells and subchronic toxicity evaluation in BALB/C mice - Aziz, Muhammad Nazirul Mubin (2021)
Osteosarcoma (OS) is an aggressive bone cancer that arises from malignant transformation of mesenchymal cells and predominantly diagnosed among children. Poor prognosis of OS patient is due to the capability of this cancer to proliferate uncontrollably and metastasize, leading to reduction of the 5 years survival rate of patients. Even with intensive treatment, the patients’ survival rate will drop significantly to 30% if diagnosed with malignant OS. Commonly prescribed chemotherapy drug like doxorubicin exhibits adverse effects including cardiotoxicity, mucositis and myelosuppression. Therefore, discovery of potential anti-cancer agent that derived from natural products and pharmacologically safe for human consumption is imperative. Curcumin is a natural polyphenolic component that is isolated from turmeric and possess wide spectrum of pharmacological benefits including anti-proliferative, anti-metastasis, antiangiogenesis as well as has an excellent safety profile. However, natural curcumin reportedly has poor cellular uptake, leading to the development of synthetically synthesized curcuminoid analog, namely (Z)-3-hydroxy-1-(2- hydroxyphenyl)-3phenylprop–2–en-1-one (DK1). The aims for this study are to assess the safety of DK1 in BALB/c mice model and to determine the anti-cancer potential of DK1 by evaluating the cytotoxicity effects, apoptosis induction as well as metastasis inhibition in both U-2 OS and MG-63 human osteosarcoma cell lines. Additionally, this study also focused on the anti-cancer mechanism induced by DK1 and to assess the expression of regulatory long non-coding RNA in human osteosarcoma cell lines. Subchronic toxicity study revealed that DK1 did not cause any toxicity effects on BALB/c mice, proven by no significant (p<0.05) alteration in the biochemical analysis, organ to body weight ratio as well as no apparent physical signs of toxicity on the organs histology. The 3-(4,5- dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) cell viability assay manifested that DK1 has successfully inhibited the proliferation of U-2 OS and MG-63 osteosarcoma cell lines with the half maximal inhibitory concentration (IC50) at 19.6 ± 0.3 μM and 23.8 ± 0.8 μM respectively without interfering the proliferation of the normal cells. To examine the morphological signs of cell death induced by the DK1, AO/PI double staining assay was performed and subsequently followed by Annexin V/FITC and cell cycle flow cytometry analysis in order to further confirm that DK1 induced cell death via apoptosis. Cell cycle analysis verified that DK1 induced apoptosis as depicted by the accumulation at Sub G0/G1 phase that was substantially (p<0.05) increased in both osteosarcoma cell lines. In this study, DK1 also exhibited an anti-metastatic potential by impeding the cell motility of U-2 OS and MG-63 osteosarcoma cell lines, as shown by the finding that the percentage of cell migration were significantly (p<0.05) decreased to 37.2 ± 7.4% and 3.5 ± 0.2 % respectively. A substantial (p<0.05) reduction in the percentage of migrated and invaded cells also can be observed in both cell lines where reduction from 100% to 44.4 ± 3.6% and 61.6 ± 1.4% was observed respectively. Additionally, DK1 also possessed an anti-angiogenic potential that was proven by the finding that the percentage of tube formation and microvessels sprouting were significantly (p<0.05) reduced. From the microarray analysis several cancer pathways such as PI3K/Akt, MAPK, NF-κB, P53 and cell cycle were successfully modulated by the DK1. In addition, DK1 also significantly (p<0.05) regulated the expression of several characterized long non-coding RNA namely HOTAIR, TUG1 and GAS5 as well as uncharacterized long non-coding RNA such as lnc-CETP-1, lnc- LOXL1-1, lnc-UBLCP1-1, and lncC17orf62-3 in both human osteosarcoma cell lines. In conclusion, DK1 could be considered as a potential candidate for anticancer therapy in near future since it was able to induce apoptosis, inhibit metastasis and regulate the lncRNA expression in osteosarcoma cell lines as well as did not exert any toxicity effects on the tested mice model in similar to natural curcumin.